Better Together: A Pilot Study on Cooking Matters for Adults With Developmental Disabilities and Direct Support Professionals. (April 2019) - Barnhart, Wesley R; Havercamp, Susan M; Lorenz, Allison; Yang, Emily A
Adults with developmental disabilities face barriers to making healthy lifestyle choices that mirror the barriers faced by the direct support professionals who serve them. These two populations, direct support professionals and adults with developmental disabilities, are likely to lead inactive lifestyles, eat unhealthy diets, and be obese. Moreover, direct support professionals influence the nutrition knowledge, attitudes, and health behaviors of the adults with developmental disabilities whom they serve. We piloted a cooking-based nutrition education program, Cooking Matters for Adults, to dyads of adults with developmental disabilities (n = 8) and direct support professionals (n = 7). Team-taught by a volunteer chef and nutrition educator, Cooking Matters for Adults uses an active learning approach to teach food preparation safety skills and nutrition knowledge to inform healthy food and beverage choices. We assessed healthy food preparation, intake of a balanced diet, healthy food and beverage choices, and cooking confidence and barriers at pre-test, post-test, and 6-months after the intervention. Among both adults with developmental disabilities and direct support professionals, positive trends in healthy food preparation, eating a balanced diet, and reduction in cooking barriers were observed at post-test and 6-months. We also qualitatively assessed knowledge of and attitudes toward healthy eating, frequency of food and beverage intake, knowledge about kitchen skills and safety, as well as overall satisfaction, cooking confidence, and acceptability of the dyad approach. Participants with developmental disabilities and direct support professionals reported that they learned about healthy food and beverage choices and various cooking skills. Participants reported confidence in skills learned and were satisfied with the intervention and approach of including adults with developmental disabilities and direct support professionals in the intervention together.